2002
DOI: 10.1042/cs103s189s
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of endothelin-1 on isolated working rat hearts before and after ischaemia and reperfusion

Abstract: Endothelin (ET) may have both detrimental (reduced coronary flow) and beneficial effects (positive inotrope, reduced arrhythmogenesis) following ischaemia. We examined the effects of ET on cardiac function during reperfusion following prolonged hypothermic cardioplegic arrest in a protocol mimicking cardiac transplantation. Isolated working rat hearts were perfused with Krebs buffer to which increasing concentrations of ET-1 or sarafotoxin S6c had been added. Identical experiments were performed after 4 h of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Studies in vivo have shown that I/R causes myocardial injury concomitantly with an increase in the content of ET-1 and the expression of preproET-1 mRNA, an effect which is attenuated by ET receptor antagonists [5]. As has been reported previously [6], in the present study, exogenous administration of ET-1 also induced ischemia-like injury in isolated rat hearts. Others have demonstrated that ET A / B receptor antagonist or ET A receptor antagonist [5,7], but not ET B receptor antagonist [8], dose-dependently reduced myocardial injury and the incidence of ventricular arrhythmia.…”
Section: Discussionsupporting
confidence: 79%
“…Studies in vivo have shown that I/R causes myocardial injury concomitantly with an increase in the content of ET-1 and the expression of preproET-1 mRNA, an effect which is attenuated by ET receptor antagonists [5]. As has been reported previously [6], in the present study, exogenous administration of ET-1 also induced ischemia-like injury in isolated rat hearts. Others have demonstrated that ET A / B receptor antagonist or ET A receptor antagonist [5,7], but not ET B receptor antagonist [8], dose-dependently reduced myocardial injury and the incidence of ventricular arrhythmia.…”
Section: Discussionsupporting
confidence: 79%
“…Free radical can cause glucose and lipid peroxidation, protein denaturation, and enzyme inactivation of cell membrane, break DNA chain in cell, induce apoptosis, and cause heart injury [ 30 , 31 ]. Endothelin (ET) can lead to myocardial ischemia necrosis [ 32 , 33 ]and damage heart structure and function through its vascular contractile effect [ 34 , 35 ]. It also can cause heart ischemia anoxemia, or even thrombosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%